2016
DOI: 10.1111/dom.12817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DPP‐4 inhibitor linagliptin and GLP‐1 receptor agonist liraglutide on physiological response to hypoglycaemia in Japanese subjects with type 2 diabetes: A randomized, open‐label, 2‐arm parallel comparative, exploratory trial

Abstract: Dipeptidyl peptidase‐4 (DPP‐4) inhibitors reduce the risk of hypoglycaemia, possibly through augmentation of glucose‐dependent insulinotropic polypeptide (GIP) action, but not that of glucagon‐like peptide‐1 (GLP‐1) on glucagon secretion. To examine this model in Japanese individuals with type 2 diabetes (T2D), the effects of the DPP‐4 inhibitor linagliptin on glucagon and other counter‐regulatory hormone responses to hypoglycaemia were evaluated and compared with those of the GLP‐1 receptor agonist liraglutid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 22 publications
(48 reference statements)
3
28
1
Order By: Relevance
“…Overall, the study suggests a lower counter‐regulatory response to mild hypoglycaemia during DPP‐4 inhibition, whereas the responses, when reducing glucose, to more severe hypoglycaemia are maintained. Previous studies have shown non‐suppressed responses during vildagliptin treatment at a 2.5 mmol/L glucose level, whereas a recent study in type 2 diabetes showed significantly suppressed cortisol, adrenaline and noradrenaline responses to hypoglycaemia at 2.5 mmol/L after treatment with the DPP‐4 inhibitor linagliptin, which is similar to our current finding of suppressed adrenaline and cortisol responses during sitagliptin treatment at a 3.5 mmol/L glucose level. These findings need to be explored in further studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Overall, the study suggests a lower counter‐regulatory response to mild hypoglycaemia during DPP‐4 inhibition, whereas the responses, when reducing glucose, to more severe hypoglycaemia are maintained. Previous studies have shown non‐suppressed responses during vildagliptin treatment at a 2.5 mmol/L glucose level, whereas a recent study in type 2 diabetes showed significantly suppressed cortisol, adrenaline and noradrenaline responses to hypoglycaemia at 2.5 mmol/L after treatment with the DPP‐4 inhibitor linagliptin, which is similar to our current finding of suppressed adrenaline and cortisol responses during sitagliptin treatment at a 3.5 mmol/L glucose level. These findings need to be explored in further studies.…”
Section: Discussionsupporting
confidence: 89%
“…We have demonstrated previously that the glucagon response to hypoglycaemia is maintained during treatment with the DPP‐4 inhibitor vildagliptin in type 2 diabetes, both in monotherapy and in combination with insulin, with results similar to those obtained with linagliptin in Japanese individuals with type 2 diabetes . These studies, however, did not examine elderly subjects.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Liraglutide exerts glucose‐lowering effects by enhancing basal and postprandial insulin secretion from pancreatic β‐cells. Therefore, it is conceivable that remaining β‐cell function is one of the critical determinants in the glucose‐lowering effects of liraglutide.…”
Section: Discussionmentioning
confidence: 99%
“…In phase III trials, semaglutide led to improved glycaemic control and decreased body weight, with a safety profile similar to other GLP‐1 receptor agonists (GLP‐1RAs) . Liraglutide, having a similar structure to semaglutide but a different pharmacokinetic profile, was found to have no effect on the counterregulatory responses to hypoglycaemia . These responses have not been evaluated in people treated with semaglutide.…”
Section: Introductionmentioning
confidence: 99%